Functional groups of woody species in semi‐arid regions at low latitudes. (3rd July 2014) - de Oliveira, Clemir Candeia; Zandavalli, Roberta Boscaini; de Lima, André Luiz Alves; Rodal, Maria Jesus Nogueira
Abstract In seasonally dry environments, woody species have different survival strategies. However, little is known about how environmental variables affect the phenology and water dynamics of these species. We aim to understand which variables initiate the vegetative phenophases of species in a tropical semiarid climate at 3°S latitude, where variation in photoperiod is minimal and rainfall is seasonal. We hypothesize that groups of species with similar vegetative phenologies, under similar conditions, are functionally similar in terms of water storage and use. We analyse the relationship between functional characteristics related to the acquisition and utilization of water, such as wood density, water storage capacity, water potential and vegetative phenology. The attributes were ordered by multidimensional scaling, and a multiple response permutation procedure was used to test consistency of the groups. Canonical correspondence analysis and Mantel tests were used to evaluate the phenophase response to environmental variables. We found four functional groups: (i) deciduous low wood density, which lose 75% of their leaves one month before the end of the rains; (ii) evergreen high wood density; (iii) early deciduous high wood density, which lose 75% of their leaves one month after the end of the rains; and (iv) late deciduous high wood density, which lose 75% of their leaves two months after the end of the rains. As expected, the vegetative phenodynamics of the deciduous high wood density group were mainly influenced by water availability. The evergreens did not show a correlation with rainfall. Only leaf shedding of the late deciduous, and the vegetative phenophases of the evergreens, responded to an increase in temperature and photoperiod. Bud‐break responded to increased photoperiod and soil humidity in the deciduous low wood density group. The foliar periodicity groups can be explained by the presence of species that differ mainly in their mechanisms of water acquisition and use.